2015
DOI: 10.1039/c4ra13395a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of shape-controllable cobalt nanoparticles and their shape-dependent performance in glycerol hydrogenolysis

Abstract: Cobalt nanorods were synthesized in polyol with using Ir as the nucleation agent and sodium stearate as the surfactant. The aspect ratio of rods can be facilely mediated by Ir/Co molar ratios. During rod growth, the solid cobalt alkoxide and stearate intermediates formed at initial stages and acted as the reservoir to control Co 2+ reduction, followed by further mediating the rod growth. Stearate played the critical role in controlling the formation of rods by its selective and covalent coating on {10-10} plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 51 publications
(94 reference statements)
1
32
0
1
Order By: Relevance
“…However, in both cases it would have been interesting to monitor the size/shape of the nanorods after the different thermal treatments and reaction in order to discard shape changes (if any) and a misinterpretation of the results. The Co 0 -hcp nanorods with mainly {10-10} planes exposed have been investigated in the glycerol hydrogenolysis and found to be more active than Co 0 -fcc spheres, demonstrating the facet-dependent performance [28]. The authors showed TEM micrographs of spent cobalt materials and observed that the surface of the rods became rough although their 1D shape was retained, evidencing the robustness of the materials dispersed in a 10 % glycerol solution under 200 °C and 3.0 MPa of H 2 for 16 h.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in both cases it would have been interesting to monitor the size/shape of the nanorods after the different thermal treatments and reaction in order to discard shape changes (if any) and a misinterpretation of the results. The Co 0 -hcp nanorods with mainly {10-10} planes exposed have been investigated in the glycerol hydrogenolysis and found to be more active than Co 0 -fcc spheres, demonstrating the facet-dependent performance [28]. The authors showed TEM micrographs of spent cobalt materials and observed that the surface of the rods became rough although their 1D shape was retained, evidencing the robustness of the materials dispersed in a 10 % glycerol solution under 200 °C and 3.0 MPa of H 2 for 16 h.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Figure 1 shows TEM micrograph of the as synthesised cobalt nanoparticles. These nanoparticles have been described previously as hexagonal rods with two conical heads (dumbbell-shaped) [28,34,35] with length of 68±12 nm and diameter of the ends (28±3 nm)…”
Section: Thermal Stability Of the Cobalt Nanoparticles Under H 2 H mentioning
confidence: 99%
“…The crystallite sizes calculated from the (10-10), (0002) and (10)(11) line broadening in the Co 50 @(Co 0.5 Sb 0.5 ) 50 sample that was annealed at different temperatures are shown in figure 7. The corresponding XRD patterns are provided in the supplementary information (Fig.…”
Section: Chemical Analysismentioning
confidence: 99%
“…(b) Evolution of the (0002) and (10-10) crystallite sizes of the hcp Co and (10-11),(10)(11)(12) and(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) crystallite sizes of the β-CoSb as a function of the Sb content.…”
mentioning
confidence: 99%
“…54 Easy functionalization property and good biocompatibility of modified molecule are the key requirements to select an effective route for prepare different sized NP. 55 Drug delivery through gold nanoparticles (AuNP) gives a versatile platform for effective drug delivery. Doxorubicin coated AuNP have reported making enhanced drug accumulation by overcoming multidrug resistance (MDR) in cancer treatment.…”
Section: Nanoparticlementioning
confidence: 99%